AIM/LIR-based fluorescent sensors—new tools to monitor mAtg8 functions. Issue 6 (3rd June 2018) - Zientara-Rytter, Katarzyna; Subramani, Suresh
ABSTRACT: Macroautophagy/autophagy, a catabolic process by which cytoplasmic materials are degraded and recycled in lysosomes/vacuoles, remains a rapidly expanding research topic with the need for constantly improved methodologies to study each step of this pathway. Recently Lee and colleagues, as well as Stolz et al., independently reported the development of new AIM/LIR-based fluorescent sensors, which mark individual endogenous mammalian Atg8-family (mAtg8) proteins without affecting the autophagic flux. When expressed in cells, each sensor selectively recognizes individual mAtg8 isoforms and distinguishes mammalian MAP1LC3/LC3 proteins from the related GABARAPs. Such selectivity was achieved by using various LC3-interacting regions with high binding affinity to either a subgroup, or a specific, mAtg8 isoform as part of the sensor. Here we discuss the utility of these sensors in autophagy research and highlight their strengths, weaknesses and future directions.